The effect of 60 days of 6° head-down-tilt bed rest on circulating adropin, irisin, retinol binding protein-4 (RBP4) and individual metabolic responses in young, healthy males - Ward, Kiera; Mulder, Edwin; Frings-Meuthen, Petra; O’Gorman, Donal J.; Cooper, Diane (Frontiers in Physiology, 2024)
Background: Alterations in the circulating concentrations and target-tissue action of organokines underpin the development of insulin resistance in microgravity and gravity deprivation. The purpose of this study was to examine changes in circulating adropin, irisin, retinol binding protein-4 (RBP4), and the metabolic response of healthy young males following 60 days of 6° head-down-tilt (HDT) bed rest, with and without reactive jump training (RJT), to explore links with whole-body and tissue-specific insulin sensitivity. To our knowledge, this is the first time that adropin, irisin, and RBP4 have been studied in HDT bed rest.Methods: A total of 23 male subjects (29 ± 6 years, 181 ± 6 cm, 77 ± 7 kg) were exposed to 60 days of 6° HDT bed rest and randomized to a control (CTRL, n = 11) or a RJT (JUMP, n = 12) group (48 sessions with ≤ 4 minutes total training time per session). Circulating adropin, irisin, and RBP4 were quantified in fasting serum before and after HDT bed rest. A subanalysis was performed a posteriori to investigate individual metabolic responses post-HDT bed rest based on subjects that showed an increase or decrease in whole-body insulin sensitivity (Matsuda index).Results: There were significant main effects of time, but not group, for decreases in adropin, irisin, Matsuda index, and liver insulin sensitivity following HDT bed rest (p < 0.05), whereas RBP4 did not change. The subanalysis identified that in a subgroup with decreased whole-body insulin sensitivity (n = 17), RBP4 increased significantly, whereas adropin, irisin, and liver insulin sensitivity were all decreased significantly following HDT bed rest. Conversely, in a subgroup with increased whole-body insulin sensitivity (n = 6), liver insulin sensitivity increased significantly after HDT bed rest, whereas adropin, irisin, and RBP4 did not change.Investigating individual metabolic responses has provided insights into changes in circulating adropin, irisin, RBP4, in relation to insulin sensitivity following HDT bed rest. We conclude that adropin, irisin, and RBP4 are candidate biomarkers for providing insights into whole-body and tissue-specific insulin sensitivity to track changes in physiological responsiveness to a gravity deprivation intervention in a lean male cohort.